Job Satisfaction Judging from the Emotional Labor - Hartini, Sri; Chairani, Marina; Siregar, Melda Kristiani; Sipahutar, Putra Indo Sema (TAZKIYA Journal of Psychology, 2020)
This study aims to determine whether there is a relationship between emotional labor and job satisfaction of teachers at the F. Tandean Tebing Tinggi college. The hypothesis is that there is a positive relationship between emotional labor and job satisfaction with teachers. The subjects of the study were 120 teachers in the School of F. Tandean Tebing Tinggi. This research uses quantitative research where the data collection uses a questionnaire. The assumption test consists of a normality test and a linearity test. The data analysis method used is the Product Moment correlation technique with the help of SPSS Statistics 25 for Windows. The results showed that there was a positive correlation between job satisfaction with emotional labor (Pearson Correlation 0.280, Sig 0.001 <p = 0.05). Contributions given emotional labor to job satisfaction amounted to 7.1 percent. The conclusion of this study is the research hypothesis in the form of a positive relationship between emotional labor and job satisfaction with teachers was accepted.